Biocompatibility assessment of spark plasma-sintered alumina-titanium cermets. (January 2016) - Guzman, Rodrigo; Fernandez-García, Elisa; Gutierrez-Gonzalez, Carlos F; Fernandez, Adolfo; Lopez-Lacomba, Jose Luis; Lopez-Esteban, Sonia
Alumina-titanium materials (cermets) of enhanced mechanical properties have been lately developed. In this work, physical properties such as electrical conductivity and the crystalline phases in the bulk material are evaluated. As these new cermets manufactured by spark plasma sintering may have potential application for hard tissue replacements, their biocompatibility needs to be evaluated. Thus, this research aims to study the cytocompatibility of a novel alumina-titanium (25 vol. % Ti) cermet compared to its pure counterpart, the spark plasma sintered alumina. The influence of the particular surface properties (chemical composition, roughness and wettability) on the pre-osteoblastic cell response is also analyzed. The material electrical resistance revealed that this cermet may be machined to any shape by electroerosion. The investigated specimens had a slightly undulated topography, with a roughness pattern that had similar morphology in all orientations (isotropic roughness) and a sub-micrometric average roughness. Differences in skewness that implied valley-like structures in the cermet and predominance of peaks in alumina were found. The cermet presented a higher surface hydrophilicity than alumina. Any cytotoxicity risk associated with the new materials or with the innovative manufacturing methodology was rejected. Proliferation and early-differentiation stages of osteoblasts were statistically improved on the composite. Thus, our results suggest that this new multifunctional cermet could improve current alumina-based biomedical devices for applications such as hip joint replacements.